Understanding India’s New Political Economy: A Great Transformation? - Ruparelia, Sanjay; Reddy, Sanjay; Harriss, John; Corbridge, Stuart (Taylor & Francis, 2011)
A number of large-scale transformations have shaped the economy, polity and society of India over the past quarter century. This book provides a detailed account of three that are of particular importance: the advent of liberal economic reform, the ascendance of Hindu cultural nationalism, and the empowerment of historically subordinate classes through popular democratic mobilizations. Filling a gap in existing literature, the book goes beyond looking at the transformations in isolation, managing to: • Explain the empirical linkages between these three phenomena • Provide an account that integrates the insights of separate disciplinary perspectives • Explain their distinct but possibly related causes and the likely consequences of these central transformations taken together By seeking to explain the causal relationships between these central transformations through a coordinated conversation across different disciplines, the dynamics of India’s new political economy are captured. Chapters focus on the political, economic and social aspects of India in their current and historical context. The contributors use new empirical research to discuss how India’s multidimensional story of economic growth, social welfare and democratic deepening is likely to develop. This is an essential text for students and researchers of India's political economy and the growth economies of Asia.
Keywords: India; business & economics; ethnic studies